Nurse manager succession planning: synthesis of the evidence. (20th September 2013) - Titzer, Jennifer; Phillips, Tracy; Tooley, Stephanie; Hall, Norma; Shirey, Maria
<x xml:space="preserve">Abstract</x> Aim The literature supporting nurse manager succession planning is reviewed and synthesised to discover best practice for identifying and developing future nurse managers. Background Healthcare succession planning practices are lacking. Nurse managers are historically selected based on clinical skills and lack formal leadership preparation. Evaluation A systematic literature search appraises and summarises the current literature supporting nurse manager succession planning. Multiple reviewers were used to increase the reliability and validity of article selection and analysis. Key issues New nurse managers require months to adapt to their positions. Deliberate nurse manager succession planning should be integrated in the organisation's strategic plan and provide a proactive method for identifying and developing potential leaders. Conclusion Organisations that identify and develop internal human capital can improve role transition, reduce nurse manager turnover rates and decrease replacement costs. Despite the clear benefits of succession planning, studies show that resource allocation for proactive, deliberate development of current and future nurse leaders is lacking. Additionally, systematic evaluation of succession planning is limited. Implications for nursing management Deliberate succession planning efforts and appropriate resource allocation require strategic planning and evaluation methods. Detailed evaluation methods demonstrating a positive return on investment utilising a cost–benefit analysis and empirical outcomes are necessary.